2021
DOI: 10.1080/14786419.2021.2015594
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-ESI-MS/MS profiling and hepatoprotective activities of Stevia leaves extract, butanol fraction and stevioside against radiation-induced toxicity in rats

Abstract: Stevioside is the major component of Stevia rebaudiana (Bertoni) leaves, family Asteraceae. UPLC-ESI-MS/MS analyses of leaves total methanol extract (TEx) and standardized butanol fraction (BF, 113.5 mg stevioside/g) were performed herein, revealing steviol glycosides, caffeoylquinic acid derivatives, flavonoids, and sesquiterpenoids. Their hepatoprotective activities against radiation-induced toxicity were evaluated compared to pure stevioside. Rats pretreatment with stevioside, TEx, and BF orally for 7 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Natural products derived from fungi or other biological sources are inexpensive, environmentally friendly, and play an important role in alleviating these types of problems [ 9 , 10 ]. Natural products provide effective alternatives and promising sources for many bioactivities [ 11 , 12 , 13 , 14 , 15 ]. Discovering larvicides from marine sources with biodiversity may be another approach to mosquito control.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products derived from fungi or other biological sources are inexpensive, environmentally friendly, and play an important role in alleviating these types of problems [ 9 , 10 ]. Natural products provide effective alternatives and promising sources for many bioactivities [ 11 , 12 , 13 , 14 , 15 ]. Discovering larvicides from marine sources with biodiversity may be another approach to mosquito control.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of antibiotics with natural products may not only circumvent resistance, but also decrease the dose used, consequently, reducing side effects [ 17 , 18 ]. Plant-derived compounds are ideal candidates due to their efficacy and considerably low side effects [ 19 , 20 , 21 , 22 ]. In phenolics, multiple mechanisms of antibacterial activity have been described; some compounds act by destabilizing cell membranes, thus, helping the internalization of antibiotics [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants are usually rich in bioactive phytochemicals to which the biological effects are mainly attributed 26–30 . In the current study, all the tested oil samples revealed trans -anethole as the major component and it was observed that the best extraction methodology was the one assisted by microwaves (MAE), this came in accordance with previous data reported by Cai et al.…”
Section: Resultsmentioning
confidence: 99%